Structural study of porous Si with different crystal orientation fabricated using two-step alternating current photo-electrochemical etching technique / Fatimah Zulkifli ... [et al.] - Zulkifli, Fatimah; Radzali, Rosfariza; Abd Rahim, Alhan Farhanah; Mahmood, Ainorkhilah; Abu Bakar, Aslina (Universiti Teknologi MARA, 2021)
Two different crystal orientation of n-type Si substrates n(100) and n(111) were used to fabricate porous structure using two-step Alternating Current Photo- Electrochemical (ACPEC) etching technique. This research aims to investigate the difference of porous structure and properties for different orientation of n-type Si substrate. In this work, before alternating current (AC) was supplied, the samples were immensed in HF:Ethanol for 10 minutes. Then, each sample were etched at 20 mA/cm2 current density for 30 minutes. The porous Si samples were then characterized for Field Emission Scanning Electron Microscopy (FESEM), Atomic Force Microscopy (AFM) and High Resolution X-ray Diffraction (HR-XRD) to study the surface morphology of the samples. The results obtained showed that porous Si with orientation of (100) has higher pore density formation, higher surface roughness value in RMS and deeper pore depth with improved crystalline quality compared to Si with orientation of (111).